A ceramic microbridge microfluidic chip to study osteogenic differentiation of mesenchymal stem cells in bioactive ceramic immune microenvironment - Sheng Ye; Quanle Cao; Panxianzhi Ni; Shuting Xiong; Meng Zhong; Tun Yuan; Jing Shan; Jie Liang; Yujiang Fan; Xingdong Zhang (Bioactive Materials)
Bioactive ceramics have been used in bone tissue repair and regeneration. However, because of the complex in vivo osteogenesis process, long cycle, and difficulty of accurately tracking, the mechanism of interaction between materials and cells has yet to be fully understood, hindering its development. The ceramic microbridge microfluidic chip system may solve the problem and provide an in vitro method to simulate the microenvironment in vivo. Nevertheless, the complex microenvironment parameters of the chip system need to be studied in detail. Computer simulation bionics can provide clues for the setting of microenvironment parameters. This study used a computational bionic model to simulate the bone growth process in the presence of immune-related factors. The osteoblast differentiation of mesenchymal stem cells of calcium phosphate ceramics in a macrophage-dominated immune microenvironment was studied using a microfluidic chip system. The computational biomimetic model and microfluidic chip findings were basically consistent with the reported results of the animal experiments. These findings suggest that studying the osteogenic behavior of calcium phosphate ceramics using a microfluidic chip model is feasible. The method model provided in this study can be extended to other biomaterials, providing a viable path for their research and evaluation.